2006
DOI: 10.1016/j.palaeo.2006.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Pedogenic carbonates as a proxy for palaeo-CO2 in the Palaeozoic atmosphere

Abstract: According to a model by Cerling (1991Cerling ( , 1999, the carbon isotope composition of calcretes should depend on the soil type and the CO 2 -concentration in the atmosphere. We have tested Cerling's model by investigating 14 Palaeozoic sections with soil profiles. A large number of carbonate types of different genetic origin exist in the localities examined. Comparing the Palaeozoic samples with recent and subrecent calcretes, it can be demonstrated that anhedral, cryptocrystalline (<10 µm) and subhedral mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…5b) surrounded by a coarser microcrystalline matrix (cf. Wright & Tucker, 1991;Quast, Hoefs & Paul, 2006). Occasional (< 1 %) 'floating' grains of very fine quartz (95 μm) are observed that have been replaced by the growth of carbonate (Fig.…”
Section: B Results: Petrographymentioning
confidence: 99%
“…5b) surrounded by a coarser microcrystalline matrix (cf. Wright & Tucker, 1991;Quast, Hoefs & Paul, 2006). Occasional (< 1 %) 'floating' grains of very fine quartz (95 μm) are observed that have been replaced by the growth of carbonate (Fig.…”
Section: B Results: Petrographymentioning
confidence: 99%
“…However, it can also be a later diagenetic fabric in which the crystal 458 contacts are characteristically concavo-convex (Fig. 7C), and enclose smaller patches of 459 microcrystalline dolomite (Quast et al, 2006). Most of the carbonate found in the palaeosols 460 in the Ballagan Formation exhibits alpha textures, although the calcified root traces (Fig.…”
Section: Protosols 408mentioning
confidence: 99%
“…Deviations from these assumptions reveal uncertainties in chronological and reconstructional studies based on PC (Cerling, 1991;Pustovoytov and Leisten, 2002;Quast et al, 2006). Because recrystallization rates depend on various biotic and abiotic factors (Gocke et al, 2011b;Gocke and Kuzyakov, 2011), the resulting errors will differ, especially where recrystallization is relatively fast, e.g.…”
Section: Recrystallization Of Soil Carbonatesmentioning
confidence: 99%
“…Moreover, the difference of δ 13 C values of the remaining GC to that of PC (Fig. 10) leads to a less negative δ 13 C of PC (Pendall et al, 1994;Quast et al, 2006) and consequently to doubtful paleoecological interpretations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%